2017
DOI: 10.1002/aqc.2760
|View full text |Cite
|
Sign up to set email alerts
|

Genetic population structure of harbour seals in the United Kingdom and neighbouring waters

Abstract: Abstract1. In the United Kingdom (UK), several harbour seal (Phoca vitulina) populations have been declining over the past decade. In order to understand the effect of these changes in abundance, this study seeks to determine the population structure of harbour seals in the UK, and in Scotland in particular, on a wider and finer spatial scale than has previously been reported.2. Harbour seals were genotyped from 18 different localities throughout the UK and neighbouring localities in mainland Europe, at 12 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…As throughout the study the growth rate of the total Wadden Sea population did not exceed the intrinsic rate of increase for the species, it seems unlikely that the growth was influenced, let alone fuelled by immigration from colonies outside the Wadden Sea. This is supported by earlier findings that indicate the Wadden Sea harbour seal population being a distinct genetic population [ 34 , 35 ] though recent findings indicated there was a strong connection with harbour seals from France and southern UK [ 64 ]. In addition to this, the occurrence of virus epizootics did affect population growth temporarily, but did not prevent the population from continuing its recovery.…”
Section: Discussionsupporting
confidence: 83%
“…As throughout the study the growth rate of the total Wadden Sea population did not exceed the intrinsic rate of increase for the species, it seems unlikely that the growth was influenced, let alone fuelled by immigration from colonies outside the Wadden Sea. This is supported by earlier findings that indicate the Wadden Sea harbour seal population being a distinct genetic population [ 34 , 35 ] though recent findings indicated there was a strong connection with harbour seals from France and southern UK [ 64 ]. In addition to this, the occurrence of virus epizootics did affect population growth temporarily, but did not prevent the population from continuing its recovery.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, recent tagging and genetic studies indicate that especially juvenile harbour seals undertake movements across much greater distances than previously reported, and thus potentially could have played a larger role in transporting PDV longer distances. For instance, Wadden Sea harbour seals have been shown to undertake foraging trips of a couple of hundred kilometres into the North Sea (Dietz et al, 2013;Tougaard et al, 2008;Aarts et al, 2016), and recent population genetic analyses suggested movements among the seals in southern England, France and the Dutch Wadden Sea (Olsen et al, 2017). Likewise, tagging of harbour seals in the fall and early winter of 2016 provided the first documented movements from a haul-out in southern Kattegat to the central Limfjord (Rune Dietz and collaborators, unpublished) by an animal that has now been genetically determined to originate from the Limfjord (Morten Tange Olsen, unpublished).…”
Section: Spread Of Pdv In 2002 Through Multiple Transmission Eventsmentioning
confidence: 99%
“…A prime example of changing dynamics in a metapopulation is the UK harbour seal (Phoca vitulina), which has been monitored for decades to provide regional population trends, local movement and genetic datasets (15)(16)(17)(18). The UK-wide abundance of harbour seals is currently 42,100 seals (95% CI: 34,500 -52,300), which is comparable to the estimate 20 years ago at 45,550 (95% CI: 37,250 -60,750) (17).…”
Section: Introductionmentioning
confidence: 99%